THE INFLUENCE OF SELF EFFICACY AND LOCUS OF CONTROL ON EMPLOYEE PERFORMANCE AT BPJS KESEHATAN - Nisa, Nur Ainun; Sugianto, Sugianto; Jurana, Jurana; Mustamin, Mustamin (Penelitian dan Pengembangan Ilmu, 2025)
This study tends to discover the influence of Self Efficacy and Locus of Control on employee performance. The research employed a quantitative approach with data collected using questionnaires from 30 respondents, then examined using WarpPLS 7.0. The outcomes implied that Self Efficacy and Locus of Control on employee performance had a significant positive effect. Employees who have high levels of Self Efficacy aim to be more confident, proactive, and able to manage stress well, so as to increase work productivity. Meanwhile, the internal Locus of Control encourages employees to be more responsible for their work, increase motivation, and support the achievement of organizational goals. The results of this research enhance BPJS Kesehatan Palu Branch Office in improving employee performance through strengthening Self Efficacy and Locus of Control.